"Multiethnic Pioneers": Representation of Korean Agrarian Villages in Manshū gurafu and the Vision of a Multiethnic State. (22nd July 2022) - Kang, Inhye
Abstract: Manchuria (also known as Manchukuo) was a puppet state established by Japanese empire after the Mukden Incident on September 18, 1931. From its genesis, Manchuria sought to create a positive image of itself both for domestic Japanese and international audiences. This paper focuses on Manshū gurafu (Manchuria Graph), a magazine published by the South Manchuria Rail Company. The magazine is important as a specialist photographic publication and has recently received much attention, particularly thanks to the fact that it was edited by well-known Japanese photographer Fuchikami Hakuyō. This article focuses on images of the colonized, specifically examining visual representations of Koreans residing in Manchuria and other travel-related photography. In this way, the article demonstrates how photographic images of Koreans in Manchuria happen to reveal conflicts within Manchurian state ideology, including the concept of Harmony among Five Races. Also addressed are the ways in which the visual mechanism of photomontage visualized both the symbolic meaning and inherent conflicts of the notion of multiethnicity in Manchuria.